Система морфізмів для просторів невизначеності та її застосування - Diduk, N. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A system of morphisms — the main instrument for further development of the uncertainty theory is built. It is immediately used for search of uncertainty spaces images by given functions. Factorspaces and projections are the most important particular cases of images. It is proved that such projections of two-dimensional uncertainty spaces in probability case are the Shannon uncertainty spaces which correspond common projections of two-dimensional probability distributions. It proves that the apparatus, which has been built, checks well with the probability theory apparatus.